2016
DOI: 10.1128/aac.02657-15
|View full text |Cite
|
Sign up to set email alerts
|

Sequential Evolution of Vancomycin-Intermediate Resistance Alters Virulence in Staphylococcus aureus: Pharmacokinetic/Pharmacodynamic Targets for Vancomycin Exposure

Abstract: e Staphylococcus aureus possesses exceptional virulence and a remarkable ability to adapt in the face of antibiotic therapy. We examined the in vitro evolution of S. aureus in response to escalating vancomycin exposure by evaluating bacterial killing and the progression of resistance. A hollow-fiber infection model was utilized to simulate human doses of vancomycin increasing from 0.5 to 4 g every 12 h (q12h) versus a high inoculum (10 8 CFU/ml) of methicillin-resistant S. aureus (MRSA) USA300 and USA400. Host… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
11
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 18 publications
(11 citation statements)
references
References 44 publications
0
11
0
Order By: Relevance
“…Several in vitro studies in dynamic systems including the HF model ( Nicasio et al, 2012 ; Lenhard et al, 2016 ) have investigated the antibacterial activity of drugs combined with vancomycin against planktonic S. aureus . However, the use of dynamic in vitro systems, such as the CDC biofilm device or others, to study the effects of combinations on biofilm is rarely reported.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Several in vitro studies in dynamic systems including the HF model ( Nicasio et al, 2012 ; Lenhard et al, 2016 ) have investigated the antibacterial activity of drugs combined with vancomycin against planktonic S. aureus . However, the use of dynamic in vitro systems, such as the CDC biofilm device or others, to study the effects of combinations on biofilm is rarely reported.…”
Section: Discussionmentioning
confidence: 99%
“…These results are in agreement with previous studies which demonstrated the low activity of vancomycin on large bacterial inocula ( LaPlante and Rybak, 2004 ; LaPlante and Woodmansee, 2009 ) and on biofilms ( Hogan et al, 2016 ). One study involving a HF model showed that a peak concentration as high as 80 mg/L was needed to achieve bactericidal activity against a large inoculum of a MRSA strain with a MIC of 1 μg/mL for vancomycin ( Lenhard et al, 2016 ). One proposed explanation for the inoculum effect and reduced efficacy of vancomycin is that bacteria at high density are in a stationary growth phase with low dividing rate and low cell wall synthesis ( Brown et al, 1988 ; Lamp et al, 1992 ).…”
Section: Discussionmentioning
confidence: 99%
“…In this section we explore the implications when they are exposed sequentially. Previous studies have explored the effects of sequential exposure of both different antibiotics (Lenhard et al, 2015;MacGowan and Bowker, 1998;Miller et al, 1996) and antibiotics and temperature (Andrade-Linares et al, 2016;Hilker et al, 2016;Manrique et al, 2016;Rangel, 2011). Even transient exposure to a stressor can modify how an organism responds to subsequent stress.…”
Section: Sequential Exposure To Antibiotics and Temperaturementioning
confidence: 99%
“…Similarly, relative RNAIII expression also transiently increased 410x baseline when USA 300 was exposed to 2 g of vancomyin q12h in a previous HFIM experiment. 17 In the present study, we sought to characterize the impact of agr-dysfunction on linezolid pharmacodynamics. Time-killing studies evaluating S. aureus with a group I, II or IV agr system suggest agr dysfunction did not significantly alter the activity of linezolid.…”
Section: Clinical Failures Of Vancomycin Against Methicillin-resistantmentioning
confidence: 99%